(untitled) (Conferencea, 2022)
Successful participation in competitions depends not only on the high level of physical, technical and tactical preparation of the athlete, but also on his psychological preparation. as a mandatory element, the athlete must prepare psychologically for certain conditions of sports activities in order to open reserve possibilities.